Implementation Of Article 38 Point M Of Paser District Regulation Number 7 Of 2016 Concerning Village Head Elections Case Study Of Pulau Rantau Village Head Elections - Sari, Husna; Faralita, Ergina (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The legal product on the election of village heads in Paser Regency is Regional Regulation No. 07/2016 on the Election of Village Heads. This regulation stipulates that each village head must fulfill the requirement of being willing to reside in the village where he/she serves from the time of inauguration. This Regional Regulation also states that the village head can be dismissed because he no longer meets the requirements as a village head. in this dismissal mechanism, the Village Consultative Body proposes to the regent through the sub-district head. In Pulau Rantau Village, there is an assumption that the elected village head does not live in a permanent house in Pulau Rantau Village during his/her term of office as stipulated in Regional Regulation No. 07/2016 on Village Head Elections. This has happened for a long time before the village head who served for 2 periods with an interval of 12 years also did not live in the village during his tenure. The Village Consultative Body as the legislative body at the village level also did not conduct deliberations to propose the dismissal of the village head as stipulated in Regional Regulation of Paser Regency Number 07 of 2016 concerning Village Head Elections. Keywords: implementation, local regulation, village head election Abstrak Produk hukum tentang pemilihan kepala desa di Kabupaten Paser yakni Peraturan Daerah Nomor 07 Tahun 2016 Tentang Pemilihan Kepala Desa. peraturan ini mengatur bahwa setiap kepala desa wajib memenuhi persyaratan yakni bersedia bertempat tinggal di desa dimana dia menjabat terhitung sejak dilantik. Di dalam Peraturan Daerah ini juga menyebutkan kepala desa dapat diberhentikan karena tidak lagi memenuhi persyaratan sebagai kepala desa. dalam mekanisme pemberhentian ini Badan Permusyawaratan Desa mengusulkan kepada bupati melalui camat. Di desa Pulau Rantau terdapat asumsi bahwa kepala desa selama menjabat, kepala desa yang terpilih tidak bertempat tinggal menetap dengan rumah permanen di Desa Pulau Rantau sebagaimana diatur di dalam Peraturan Daerah Nomor 07 Tahun 2016 Tentang Pemilihan Kepala Desa. Hal ini sudah terjadi sejak lama sebelumnya kepala desa yang menjabat selama 2 periode dengan selang waktu 12 tahun juga tidak bertempat tinggal di desa selama menjabat. Badan Permusyawaratan Desa selaku lembaga legislatif di tingkat desa juga tidak melakukan musyawarah usul pemberhentian kepala desa sebagaimana Peraturan Daerah Kebupaten Paser Nomor 07 Tahun 2016 Tentang Pemilihan Kepala Desa. kata Kunci: Implementasi, peraturan daerah, kepala desa